Lipid Profiles and Signals for Long Life. (November 2015) - Schroeder, Elizabeth A.; Brunet, Anne
Abstract : Historically, fat was considered detrimental to health and lifespan. However, lipidomics, the quantification of all lipid molecules in a biological sample, and genetic studies in model organisms are revealing specific fats that may promote longevity. These emerging findings provide insight into the complex relationship between lipids and longevity.